2015
DOI: 10.1039/c5cp03204k
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory calculations of the hydrazine decomposition mechanism on the planar and stepped Cu(111) surfaces

Abstract: We have investigated the adsorption of hydrazine (N2H4) and its reactivity on terraces and steps of Cu(111) surfaces by first-principles calculations in order to gain insight into the hydrazine decomposition mechanism. We have investigated different possibilities for the N-N and N-H bond cleavage for any intermediate states by analysing the reaction and barrier energies of each elementary step. We have found that hydrazine dehydrogenation via N-H bond scission is neither energetically nor kinetically favourabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…44 Thus, the Ni located at the vertex of the cluster could be a source of electrons for an eventual reaction with electron receptor molecules approaching the cluster from the gas phase. 50 Analysing the electron density difference between the cluster and the surface (Fig. 3), we have conrmed a charge accumulation between the Ni atoms directly bonded to the surface and the surface atoms; there is no charge relocation between the top Ni atom which remains fully metallic.…”
Section: Resultsmentioning
confidence: 98%
“…44 Thus, the Ni located at the vertex of the cluster could be a source of electrons for an eventual reaction with electron receptor molecules approaching the cluster from the gas phase. 50 Analysing the electron density difference between the cluster and the surface (Fig. 3), we have conrmed a charge accumulation between the Ni atoms directly bonded to the surface and the surface atoms; there is no charge relocation between the top Ni atom which remains fully metallic.…”
Section: Resultsmentioning
confidence: 98%
“…We did not observe, however, a loss of the total N1s peak intensity, which suggests that the reaction product is still adsorbed on the surface. It is most probably caused by the fact that NH 2 in its less stable monomeric (amidogen) and more stable dimeric (hydrazine) forms are known to adsorb strongly to the Cu surfaces …”
Section: Figurementioning
confidence: 89%
“…It is most probably caused by the fact that NH 2 in its less stable monomeric (amidogen) and more stable dimeric (hydrazine) forms are known to adsorb strongly to the Cu surfaces. [27,28] The presence of the Cl-superstructure has a remarkably different influence on the chemical properties of Cu(001). The BEs of both N1s peaks and the C1s peak originating from 2HTPP after its cold-deposition (T = 100 K) on Cl/Cu (Figure 2c,d) are significantly lower than the respective BEs on N/Cu (Figure 2a,b) or on other substrates including Au(111), Ag(111), Cu (001) and O/Cu(001) [23,26,29] and amount to 398.9 eV, 396.8 eV and 283.7 eV for pyrrolic N1s, iminic N1s and C1s, respectively.…”
mentioning
confidence: 99%
“…Density functional theory (DFT) is commonly used to determine the energy pro le along the reaction pathway that will be employed in the micro-kinetic modelling. 26,27 We have successfully investigated the dissociative adsorption of hydrazine (N2H4) on the planar and stepped Cu(111) surfaces by rst-principles calcula-tions, 28 where the thermodynamic and kinetic potential energy surface (PES) showed that intermolecular dehydrogenation of hydrazine to produce NH3 and N2 is the favoured route among the explored reaction network. 28 Based on the identi ed mechanism, we have established a micro-kinetic model to simulate a batch reactor where hydrazine is in contact with the planar Cu(111) surface, using 52 elementary reactions including adsorption, desorption, and reactions on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 We have successfully investigated the dissociative adsorption of hydrazine (N2H4) on the planar and stepped Cu(111) surfaces by rst-principles calcula-tions, 28 where the thermodynamic and kinetic potential energy surface (PES) showed that intermolecular dehydrogenation of hydrazine to produce NH3 and N2 is the favoured route among the explored reaction network. 28 Based on the identi ed mechanism, we have established a micro-kinetic model to simulate a batch reactor where hydrazine is in contact with the planar Cu(111) surface, using 52 elementary reactions including adsorption, desorption, and reactions on the surface. We have evaluated the eff ects of temperature, initial N2H4 coverage and heating rate on a temperature-programmed reaction (TPR), as well as the selectivity towards the formation of NH3, N2, and H2, resulting in an excellent agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 99%